Simulasi Software Defined Network (SDN) Untuk Manajemen Jaringan Data PT. Chevron Pasifik Indonesia - Angreany Yasmin; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The rapid development of telecommunications requires better network technology. Computer networks are a very important and fundamental part of the development of network technology. There are still some unsatisfactorythings in the conventional network architecture such as non-centralized networks that cause difficulty in managing networks on a large scale. Centralized network is needed to be able to control network traffic more flexibly. SDN (Software Defined Network) is a centralized network concept that physically separates the control and forwading plane. In terms of capabilities, SDN is able to monitor networks more efficiently than conventional networks. This research applied a SDN network at PT Chevron. Mininet was used to design and simulate SDN networks at PT Chevron. The simulation results of network streaming audio show a delay of 12.81 m / s, throughput of 0.291 mbit / sec and packet loss of 0%. The simulation results show better performance compared to conventional networks that are currently still used by PT Chevron. Keywords:Network, SDN, Delay, Throughput, Packet loss.